SIX ELEMENTS AFFECTING LANGUAGE LEARNER SYSTEMS - Masruri, Muhammad Zen (Center for the Research and the Community Service, Islamic Institut of Hasanuddin Pare - Kediri, 2024)
There has been a lot of discussion about understanding and describing second language acquisition. This document offers a summary of error analysis in the field. It presents a new and intriguing angle on learner English in comparison to previous studies on second language acquisition. Research on mistakes made by child language learners focuses on the cognitive and linguistic processes involved in learning a language. When acquiring a second language, there are six factors that can impact and define the systems of the language learner, such as universal hierarchy of difficulty, intralingual interference, sociolinguistic context, modality, age, successions of approximative systems. Viewing the rough language systems of learners not as issues to be eliminated, but as important phases in learning the target system, could lead to a better comprehension of language overall and a more compassionate method of teaching it.